2021
DOI: 10.2147/copd.s301579
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Efficacy of Smoking Cessation Treatment Among Patients with COPD in China

Abstract: Background Smoking cessation is a key intervention for all smokers with chronic obstructive pulmonary disease (COPD). Poor treatment adherence is a challenge in clinical practice that might contribute to the lower efficacy of medication (eg, oral drug). However, it is unclear what factors will influence adherence among smokers with COPD. Methods This study was based on an open-label randomized controlled trial (RCT) of varenicline and bupropion for smoking cessation amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Due to the distinct packaging of the medications, it was not feasible to blind the participants or the researchers administering the treatments. Additional details about the random concealment are available elsewhere 19 …”
Section: Methodsmentioning
confidence: 99%
“…Due to the distinct packaging of the medications, it was not feasible to blind the participants or the researchers administering the treatments. Additional details about the random concealment are available elsewhere 19 …”
Section: Methodsmentioning
confidence: 99%
“…Moy et al [32] showed that participant readiness and confidence at the onset of oxygen therapy were associated with high short-and medium-term adherence levels. An RCT by Qin et al [33] examined the adherence of patients with COPD taking varenicline and bupropion for smoking cessation. Factors such as older age, higher level of education, the greater number of previous quit attempts, greater self-efficacy, preparation for smoking cessation, perceived risks of smoking, and longer duration of COPD were determinants of higher adherence to treatment recommendations (P < 0.05).…”
Section: Medication Adherence In Copdmentioning
confidence: 99%
“… 23 A study suggested that good adherence to smoking cessation treatment could significantly improve smoking cessation efficacy in Chinese smokers with COPD. 24 Therefore, poor treatment adherence also challenges the efficacy of pharmacotherapy. To make matters worse, pharmacotherapy for smoking cessation in China is not as common as they are abroad.…”
Section: Introductionmentioning
confidence: 99%